The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1210/jc.2016-3292
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral fractures and bone mineral density in patients with idiopathic hypoparathyroidism on long term follow-up

Abstract: Despite increased BMD, prevalence of vertebral-fractures is greater in patients with IH, especially in postmenopausal women and those on anticonvulsant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…Our patients were operated on at different places by different surgeons, which could have contributed to the high rate of hypoparathyroidism. The median age of presentation of PHPT and SIHP was similar to other published reports from India . PHPT is reported to be more common in females; however, our data pertain to male subjects only, precluding any comparison .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our patients were operated on at different places by different surgeons, which could have contributed to the high rate of hypoparathyroidism. The median age of presentation of PHPT and SIHP was similar to other published reports from India . PHPT is reported to be more common in females; however, our data pertain to male subjects only, precluding any comparison .…”
Section: Discussionsupporting
confidence: 88%
“…Previous published reports from major academic institutes show data pertaining to a few hundred patients with parathyroid disorders over a long‐term follow‐up . This suggests the presence of a huge burden of undiagnosed disease in the community, and there is an urgent requirement of identifying them to prevent morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of fractures, in general, has been described as comparable to that in control populations (34,145). A pioneer prospective study with radiological assessment of vertebral fractures has shown increased morphometric fractures in women with postsurgical hypoparathyroidism (B) (153), a finding confirmed by other authors (154). Monitoring of bone mass using dual-energy X-ray absorptiometry (DXA) has little value during long-term follow-up of patients with hypoparathyroidism, noting that the BMD tends to increase with the duration of the disease (155).…”
Section: Musculoskeletal Manifestationsmentioning
confidence: 79%
“…It is well known that primary hyperparathyroidism causes increased bone turnover and reduced BMD, especially at the cortical bone . On the contrary, idiopathic hypoparathyroidism (IHP) cases often have reduced bone turnover and increased BMD, mainly at the trabecular, than the general population . Compared with IHP and non‐surgical hypoparathyroidism patients, PHP subjects, especially pseudohypoparathyroidism type 1b (PHP1B), tend to have lower BMD, indicating incomplete skeletal resistance to PTH may exist .…”
Section: Discussionmentioning
confidence: 99%